Natural attenuation of sulfometuron-methyl in seawater: Kinetics, intermediates, toxicity change and ecological risk assessment. (1st July 2022) - Shao, Siyuan; Wu, Jiangyue; Meng, Fanping; Liu, Jiaqi
Abstract: This research aims to evaluate the environmental feasibility of sulfometuron-methyl (SM) as a growth inhibitor for restricting the growth of Spartina alterniflora . To achieve this purpose, the natural attenuation characteristics, ecological risk, degradation pathway, and comprehensive toxicity changes of SM in seawater were investigated under the simulated marine environmental conditions of Jiaozhou Bay, China. The natural attenuation of SM in seawater followed first-order reaction kinetics with a rate constant ( K ) of 0.0694 d −1 and a half-life of 9.99 days. When photolysis, hydrolysis, and biodegradation pathways act alone, the rate constants K of SM were 0.0167, 0.0143, and 0.0099 d −1 respectively, indicating that their contributions to the total removal of SM decreased in turn. The calculation results of risk quotient (RQ) showed that the seawater containing 10 mg/L of SM demonstrated a very high risk to marine diatom Skeletonema costatum before and after 21 days of attenuation with RQ values of 24.46 and 6.32, respectively, however, the risk to other marine organisms (fish, crustaceans, and bivalves) decreased from moderate (RQ < 1) to low (RQ < 0.01). Four attenuation products of SM were identified and two degradation pathways of SM in seawater were proposed. Based on the rate of inhibition of bioluminescence, SM in seawater was not harmful to Photobacterium phosphoreum T3, whereas the toxicity of seawater containing SM increased with the extension of attenuation time, suggesting the formation of intermediate products with high aquatic toxicity. According to the toxicity values predicted by ECOSAR, the toxicity of one identified attenuation product was higher than that of SM. To the best of our knowledge, this is the first report on the attenuation characteristics and toxicity changes of SM in seawater. The results indicated that the toxicity of both SM and its degradation products to non-target marine organisms should be considered in evaluating the feasibility of SM in controlling coastal Spartina alterniflora . Graphical abstract: Image 1 Highlights: The natural attenuation of SM in seawater followed first-order reaction kinetics. Photolysis, hydrolysis, and biodegradation all contribute to SM removal. Toxicity of seawater containing SM to P. phosphoreum increased with attenuation. Four intermediate products were identified during SM attenuation. 2-Amino-4, 6-dimethylpyrimidine was the intermediate with higher toxicity than SM.